2017
DOI: 10.1016/j.ejogrb.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of female sexual dysfunction in Brazil: A systematic review

Abstract: The aim of this systematic review is to investigate the prevalence of female sexual dysfunction in the Brazilian population. This is a systematic review conducted in July 2016 in which four databases were searched: MEDLINE/Pubmed, Scopus, LILACS, and Cinahl. Two investigators extracted the primary data, which were fully analyzed, and applied the inclusion/exclusion criteria. The search found 113 results, and 20 of them compounded the scope of this study. Only four of the studies showed good methodology quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 35 publications
2
34
1
16
Order By: Relevance
“…Both older age and feeling depressed are known to be associated with sexual problems in PWE. 26,27 As being in a relationship may provide patients with more opportunities for sexual activity, this may mean that any sexual problems are recognized more readily than in those living alone. In a study by Fisher et al, 6 32% of the patients reported living with a constant fear of the next seizure;…”
Section: Psychosocial Problemsmentioning
confidence: 99%
“…Both older age and feeling depressed are known to be associated with sexual problems in PWE. 26,27 As being in a relationship may provide patients with more opportunities for sexual activity, this may mean that any sexual problems are recognized more readily than in those living alone. In a study by Fisher et al, 6 32% of the patients reported living with a constant fear of the next seizure;…”
Section: Psychosocial Problemsmentioning
confidence: 99%
“…Despite the lack of consensus about the definition of FSD, FSD is generally defined as ‘the various ways in which a woman is unable to participate in a sexual relationship as she would wish’ . According to recent global figures, around 40% of women have some forms of sexual difficulty; while the prevalence of FSD ranges between 15% and 75% of the population . This notable high prevalence of FSD is alarming given the consequences of persistent dysfunction on women health; FSD was reported to have negative effects on women's quality of life and interpersonal relationship .…”
Section: Introductionmentioning
confidence: 99%
“…3 According to recent global figures, around 40% of women have some forms of sexual difficulty; while the prevalence of FSD ranges between 15% and 75% of the population. 4,5 This notable high prevalence of FSD is alarming given the consequences of persistent dysfunction on women health; FSD was reported to have negative effects on women's quality of life and interpersonal relationship. 6 Moreover, the current body of evidence shows that the FSD is not only a lifestyle disorder but also has significant associations with increased risk of cardiovascular disorders and other comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 The majority of Brazilian studies on female sexual function have investigated this among women who had some disease or were in a specific reproductive period, such as pregnancy or the menopause. 7 Studies that evaluate female sexual function among Brazilian students are scarce, but it is known that the prevalence of sexual dysfunction increases with age and multiparity and after the menopause. There are differences in female sexual function relating to the demographic variables of different countries and between individuals, such that these affect individuals' behavior and the sexual practices that they adopt.…”
Section: Introductionmentioning
confidence: 99%